Demências: identidades que adoecem - considerações sobre os aspectos psicopatológicos do envelhecimento - Zeppellini Junior, José Carlos (2008)
The human has being reaching higher and higher ages as time goes by. Civilizations all over the world are going through an irreversible process of aging populations which does not affect only several cultures but also makes us face more singular and subjective questions related to psychic work that deals with the passage from adulthood to the senile phase of life. Fundamental Psychopathology - from the point of view of its dedication and comprehension of pathic phenomenon as a constituting art of the individual offers us, a long with the psychoanalytical metapsychology and clinical practice, a rich material that assists us in the comprehension of the psychological aspects of natural aging and senility. Senile dementia present themselves as a psychopathological phenomenon, typical of this phase of life, that hot only affect the patient, but also all those around him. Therefore, the goal of this paper, besides amplifying the knowledge of this symptomathological picture, is to consider the psychopathological as a fertile and therapeutical ground, able to supply, through transference, a healthy meet among the several psychic moments and the nature of the agind body